A study to investigate the cause of failure and collapse of UMNO Tower Penang - Debbie Cynthia, Clarence Botiti (2015)
Wind-related disaster had become significant impacts in our society which responsible for the tremendous physical destruction, loss of life, injury and economic damage. On June 13th 2013, a severe thunderstorm hits Penang which lasted for about an hour. In this tragedy, the lightning arrestor pole together with several accompanying structure, the fin-shaped wall attached to a 21-storey UMNO Tower Penang came crashing down during a thunderstorm, crushing vehicles, killing two and five were severely wounded. Therefore this study was carried out to investigate the effect of wind speed to the building tower. Computational Fluid Dynamic has been used in order to examine the effect of wind to the tower. Variations of directions are tested to the tower model. From the result it clearly shows that wind load may increase up 2.71 times from North West Direction from the normal wind act to tower. Additionally historical wind speed data at the nearest meteorological station after the building was also examined. From that it was observed historical wind speed is greater compare to the design wind speed. It may also seem that this value is not the worst that can cause the structure to collapse. Historical wind speed also showed foremost wind blow come from North West Direction. It can be concluded that the possibility of the collapse are highly foreseeable due to repeatable wind speed. The effect of the geometrical shape of the tower may also increase the wind load effect to the tower. Based on the result it can be conclude the repeatable load acting to structural component of the tower may weaken the structural component. Therefore consideration of wind load direction is highly recommended during the design stage.